DDoS Detection and Mitigation via Hierarchical Adaptive Traffic Profiling and Learning-Based Control - Jangale, Chetana Digambar (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Distributed Denial-of-Service (DDoS) attacks continue to pose a significant threat to critical infrastructure and enterprise networks, with attack complexity and scale escalating substantially in recent years. Traditional threshold-based detection mechanisms exhibit limited effectiveness against adaptive adversaries and novel attack vectors. This paper presents HATPLC (Hierarchical Adaptive Traffic Profiling with Learning-based Control), a machine learning-augmented framework for real-time DDoS detection and mitigation. The proposed approach leverages hierarchical traffic decomposition combined with adaptive profiling models to establish dynamic baseline expectations. Control-theoretic principles are integrated to enable rapid mitigation response through intelligent traffic rerouting and rate-limiting policies. Evaluation on a comprehensive dataset comprising 34 labeled DDoS campaigns alongside legitimate traffic traces demonstrates detection accuracy of 94.7%, with average detection latency of 3.2 seconds. The framework achieves false positive rates of 2.1%, substantially outperforming baseline methods. Analysis across attack variants—including volumetric, protocol-based, and application-layer attacks—indicates robust performance under diverse adversarial conditions. The proposed mitigation strategy reduces attack impact by 73.2% while maintaining service availability for legitimate users with 96.8% success rate. This work contributes a practical, deployable solution addressing the detection-to-mitigation gap in contemporary network defense.